Targeting the Microbiome for Disease Diagnosis and Therapy New Frontiers for Personalized Medicine - Laterza, Lucrezia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Background: The gut microbiota is emerging as a pivotal player in the pathogenesis of many non-communicable diseases. Thus, it has been proposed as a new diagnostic and therapeutic target.Aim and scope: This Special Issue will focus on the microbiome as a potential target of new personalized therapies or diagnostic tools.History: In recent decades, the gut microbiome has been deeply investigated, and many studies have provided new information on the role of dysbiosis in many gastrointestinal and extra-gastrointestinal diseases. Recently, in addition to its phylogenetic characterization, new information has become available regarding the function of the gut microbiota, thanks to proteomic and metabolomic analyses.Cutting-edge research: The therapeutic modulation of the gut microbiota based on different strategies, including diet modification, antibiotics, prebiotics, probiotics, and, last but not least, fecal microbiota transplantation, has been tested for the treatment of various diseases. Recently, the possible applications and modalities of gut microbiota modulation have been increasingly expanding.We have collected original clinical or pre-clinical research papers and reviews focusing on the use of the microbiome for disease diagnosis, monitoring, or therapy and suggesting new possible gut microbiota-based approaches for personalized care.